Identification of novel biomarkers involved in doxorubicin-induced acute and chronic cardiotoxicity, respectively, by integrated bioinformatics - Qian, Hongyan; Qian, Yi; Liu, Yi; Cao, Jiaxin; Wang, Yuhang; Yang, Aihua; Zhao, Wenjing; Lu, Yingnan; Liu, Huanxin; Zhu, Weizhong (Frontiers in Cardiovascular Medicine, 2023)
Background: The mechanisms of doxorubicin (DOX) cardiotoxicity were complex and controversial, with various contradictions between experimental and clinical data. Understanding the differences in the molecular mechanism between DOX-induced acute and chronic cardiotoxicity may be an ideal entry point to solve this dilemma. Methods: Mice were injected intraperitoneally with DOX (20 mg/kg, once) or (5 mg/kg/week, three times) to construct acute and chronic cardiotoxicity models, respectively. Survival record and ultrasound monitored cardiac function. The corresponding left ventricular myocardium tissues were analyzed by RNA-seq to identify differently expressed genes (DEGs). GO, KEGG and GSEA found the key biological processes and signaling pathways. DOX cardiotoxicity datasets from GEO database combined with RNA-seq to identify the common genes. Cytoscape analyzed the hub genes, which were validated by quantitative real-time PCR. ImmuCo and ImmGen databases analyzed the correlations between hub genes and immunity relative markers in immune cells. Cibersort analyzed the immune infiltration and correlations between the hub genes and the immune cells. Logistic regression, receiver operator characteristic curve and artificial neural network analysis evaluated the diagnosis ability of hub genes for clinical data in GEO dataset. Results: The survival curves and ultrasound monitoring demonstrated that cardiotoxicity models were constructed successfully. In acute model, 788 DEGs were enriched in the activated metabolism and the suppressed immunity associated signaling pathways. Three hub genes (Alas1, Atp5g1 and Ptgds) were up-regulated and were negatively correlated with a colony of immune-activating cells. However, in chronic model, 281 DEGs showed G protein-couple receptor related signaling pathways were the critical events. Three hub genes (Hsph1, Abcb1a and Vegfa) were increased in chronic model. Furthermore, Hsph1 combining with Vegfa was positively correlated with dilated cardiomyopathy (DCM) induced heart failure (HF), and had high accuracy in the diagnosis of DCM induced HF (AUC = 0.898, P=0.000). Conclusion: Alas1, Atp5g1 and Ptgds were ideal biomarkers in DOX acute cardiotoxicity. However, Hsph1 and Vegfa were potential biomarkers in the myocardium in chronic one. Our research firstly provided bioinformatics and clinical evidence for the discovery of the mechanism differences and potential biomarkers of DOX-induced acute and chronic cardiotoxicity so as to find therapeutic strategy precisely.